2009
DOI: 10.1152/jn.90968.2008
|View full text |Cite
|
Sign up to set email alerts
|

Adjustments Differ Among Low-Threshold Motor Units During Intermittent, Isometric Contractions

Abstract: Farina D, Holobar A, Gazzoni M, Zazula D, Merletti R, Enoka RM. Adjustments differ among low-threshold motor units during intermittent, isometric contractions. J Neurophysiol 101: 350 -359, 2009. First published November 12, 2008 doi:10.1152/jn.90968.2008. We investigated the changes in muscle fiber conduction velocity, recruitment and derecruitment thresholds, and discharge rate of low-threshold motor units during a series of ramp contractions. The aim was to compare the adjustments in motor unit activity rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 32 publications
6
43
0
1
Order By: Relevance
“…Despite the absence of recruitment compression postrecovery, the percent increase in the mean amplitude of the MUs recruited at each threshold, averaged over all subjects, remained elevated, particularly at the latter stages of recruitment. This suggests that fatigue-induced lowering of the recruitment threshold of larger MUs was also employed postrecovery to compensate for the continued force impairment of those MUs already activated (Adam and De Luca 2003;Calder et al 2008;Carpentier et al 2001;Farina et al 2009). The slope of the regression fit to the MUAP amplitude and threshold relationship exhibited an overall tendency to increase directly postfatigue, which corresponds with the reported recruitment compression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the absence of recruitment compression postrecovery, the percent increase in the mean amplitude of the MUs recruited at each threshold, averaged over all subjects, remained elevated, particularly at the latter stages of recruitment. This suggests that fatigue-induced lowering of the recruitment threshold of larger MUs was also employed postrecovery to compensate for the continued force impairment of those MUs already activated (Adam and De Luca 2003;Calder et al 2008;Carpentier et al 2001;Farina et al 2009). The slope of the regression fit to the MUAP amplitude and threshold relationship exhibited an overall tendency to increase directly postfatigue, which corresponds with the reported recruitment compression.…”
Section: Discussionmentioning
confidence: 99%
“…Later recruited MUs have been reported to fire at a constant rate or to increase steadily (Garland et al 1994), to exhibit no significant change in discharge rate (Adam and De Luca 2005), or to show varying rates with time (Carpentier et al 2001). Although a decrease in the recruitment threshold of higher threshold MUs following fatigue is generally reported (Adam and De Luca 2003;Calder et al 2008;Carpentier et al 2001;Jensen et al 2000), some studies have observed increased recruitment thresholds for early recruited MUs (Carpentier et al 2001;Farina et al 2009). Others have reported a homogenous and monotonic decrease in the recruitment threshold of their sample MU population as fatigue progressed (Adam and De Luca 2003;Christova and Kossev 1998).…”
mentioning
confidence: 99%
“…The second issue involves the fatigability of fatigue-resistant motor units. When human volunteers performed a series of 25 ramp-up and ramp-down contractions that were minimally fatigable (9% decline in maximal voluntary contraction [MVC] force), Farina et al (2009) found that the adjustments were greatest for the first recruited motor units. As the target force for the ramp contractions was only 10% MVC force, the involved motor units were presumably fatigue resistant based on the motor unit-typing scheme.…”
Section: Motor Unit Types and Fatiguementioning
confidence: 99%
“…Despite the emphasis in the fatigue literature on the impairment of physiological processes distal to the muscle fiber action potential (Ferreira and Reid, 2008;Fitts, 2008;Place et al, 2010), even actions that involve only a modest demand are accompanied by adjustments in motor unit activity (Farina et al, 2009). The magnitude of these adjustments is underscored by the influence of load compliance on the duration that a submaximal, isometric contraction can be sustained.…”
Section: Fatigue and Fatigabilitymentioning
confidence: 99%
“…In the isometric there is a consensus response to an increase in sEMG as to alter some characteristic muscle joint as the increase in signal amplitude [13,24,25,26] changes the length and range of motion [27] and temperature [28,29,30].…”
Section: Resultsmentioning
confidence: 99%